2017
DOI: 10.1039/c7nr02232h
|View full text |Cite
|
Sign up to set email alerts
|

Hot-electron transfer from the semiconductor domain to the metal domain in CdSe@CdS{Au} nano-heterostructures

Abstract: Semiconductor-metal hybrid nanostructures are recognized as great materials due to their high level of light-induced charge separation, which has direct relevance in photocatalysis and solar energy conversion. To understand the mechanism of charge separation processes, hybrid CdSe@CdS{Au} nano-heterostructures containing Au nanoparticles (NPs) with different sizes were synthesized, and the ultrafast charge-transfer dynamics were monitored using femtosecond transient absorption spectroscopy. Steady-state optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 52 publications
4
47
0
Order By: Relevance
“…This spectral broadening up to about 800 nm can be attributed to both semiconductor‐to‐metal CT transitions and/or metal‐to‐semiconductor CT transitions depending on the nature of the excitation . The emission due to CdSe is completely quenched in the Au/CdSe HNCs due to photoinduced electron transfer from CdSe to the Au nanoparticles as shown in Figure A . The time‐resolved emission‐decay measurements also confirm the electron transfer process (Figure B).…”
Section: How Carrier Dynamics Can Benefit Qdscsmentioning
confidence: 63%
See 1 more Smart Citation
“…This spectral broadening up to about 800 nm can be attributed to both semiconductor‐to‐metal CT transitions and/or metal‐to‐semiconductor CT transitions depending on the nature of the excitation . The emission due to CdSe is completely quenched in the Au/CdSe HNCs due to photoinduced electron transfer from CdSe to the Au nanoparticles as shown in Figure A . The time‐resolved emission‐decay measurements also confirm the electron transfer process (Figure B).…”
Section: How Carrier Dynamics Can Benefit Qdscsmentioning
confidence: 63%
“…Also, broad positive photoinduced absorption appeared in the TA spectra on the longer wavelength side after 1S bleaching due to increased electron density in the Au domain (Figure ) . The electron‐transfer time from CdSe to the Au NPs was obtained from the growth of the photoinduced absorption signal and is approximately 225 fs . This positive signal decays, forming a bleach signal which does not recover in the 1 ns window, signifying the formation of a long‐lived charge‐separated state.…”
Section: How Carrier Dynamics Can Benefit Qdscsmentioning
confidence: 99%
“…The other area where the hot charge carriers are getting much attention is photocatalysis . It has been reported that the hot electron is much better photocatalyst as compared to thermal electron and also better suited for redox reactions . This has been demonstrated by Moon et al .…”
Section: Application Of Hot Charge Carriers In Different Areasmentioning
confidence: 99%
“…Hot charge carriers in semiconductor quantum dots (QDs) play a key role in several applications such as solar energy harvesting, photocatalysis, detection of toxic gases, and synthesis of various important chemicals . Starting from generation; their relaxation and extraction from QDs follow numerous steps and the efficiency of each step determines the net effect of hot charge carriers in different devices and applications .…”
Section: Introductionmentioning
confidence: 99%
“…Type II arrangement core-shell semiconductor formsa long-livedc harges eparated state after photoexcitation, in which the electrons and holes are localized in shell and core, respectively,a nd the photoexcited electron can easily be transferred to the metal oxide. [12,22] Changing the thickness of the shell QD often changes the type II structure to quasi type II structure andv ice versa. [21] Bisquert and co-workers have reported the PCE efficiency of about 7.17 %b yt ypeIIZ nTe/CdSe core-shell, which absorbsi nN IR region of the solars pectrum.…”
Section: Introductionmentioning
confidence: 99%